Inside Cover: Ring Expansions Within the Gold‐Catalyzed Cycloisomerization of O‐Tethered 1, 6‐Enynes. Application to the Synthesis of Natural‐Product‐like Macrocycles (ChemCatChem 5/2013). Issue 5 (26th April 2013) - Simonneau, Antoine; Harrak, Youssef; Jeanne‐Julien, Louis; Lemière, Gilles; Mouriès‐Mansuy, Virginie; Goddard, Jean‐Philippe; Malacria, Max; Fensterbank, Louis
<x xml:space="preserve">Abstract</x> Nature's first green is gold The cover picture shows the gold(I)‐catalyzed cycloisomerization of O‐tethered 1, 6‐enynes, which proceeds via fused tricyclic compounds with a dihydropyran moiety. As described in their Communication on p. 1096 ff., L. Fensterbank et al. continue this ring‐expansion with a two‐step sequence for the transformation of the cyclized compounds into valuable ketomacrolactones, with a motif that echoes natural products. And all this in the golden surroundings of Paris!<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>